Serum leucine-rich α2-glycoprotein is a useful biomarker for monitoring disease activity in patients with adult-onset Still's disease. (3rd September 2015) - Ha, Y-J; Kang, E-J; Lee, S-W; Park, Y-B; Lee, S-K; Song, J-S; Choi, ST
Abstract : Objective: To investigate whether serum leucine-rich α2-glycoprotein (LRG) levels are elevated in patients with adult-onset Still's disease (AOSD) and determine their correlation with disease activity parameters. Method: We enrolled 39 patients with AOSD, 47 patients with rheumatoid arthritis (RA), and 39 controls. Forty-five serum samples from the patients with AOSD were assayed for LRG using an enzyme-linked immunosorbent assay (ELISA). Comprehensive AOSD activity was determined by a modified Pouchot score. Results: Serum LRG levels were significantly elevated in patients with AOSD (128.8 ± 40.8 ng/mL) compared to those in patients with RA and in controls (33.9 ± 15.2 ng/mL, p < 0.001 and 22.4 ± 6.1 ng/mL, p < 0.001, respectively). Patients with active AOSD had significantly higher LRG levels than those with inactive disease (141.4 ± 31.3 ng/mL vs. 79.8 ± 37.1 ng/mL, p = 0.002). Serum LRG levels were positively correlated with C-reactive protein (CRP; γ = 0.387, p = 0.015), lactate dehydrogenase (LDH; γ = 0.370, p = 0.026), ferritin (γ = 0.687, p < 0.001) levels, and the modified Pouchot score (γ = 0.756, p < 0.001). Serum LRG levels decreased significantly after treatment in all six patients with active AOSD who had follow-up evaluations (p = 0.007). The best cut-off value for LRG to distinguish AOSD from RA was 67.9 ng/mL, with a sensitivity of 92.3% and a specificity of 97.9%. Conclusions: Serum LRG levels were increased in patients with AOSD and correlated well with disease activity measures. LRG may be a useful biomarker for distinguishing AOSD from RA and for monitoring the disease activity of AOSD.